Growth performance rumen fermentation and microbial population, carcass characteristic and meat fatty acid composition of goats fed diets based on oil palm kernel cake and decanter cake - Mohammed, Abdelrahim Abubakr (2013)
Shortage of feed in terms of quantity and quality is one of the most central factors that limit the development of the ruminant livestock industry in many tropical countries, including Malaysia. To overcome such problems, maximizing the use of locally available feed resources could be an alternative approach. The present study aimed to evaluate the effect of feeding diets based on palm kernel cake and decanter cake on rumen microbial population, growth performance and meat fatty acid profile of goats. In the first study, sixteen rumen-cannulated Boer X Kacang crossbred goats were used to evaluate the effect of crude palm oil, (PO), palm kernel cake (PKC) and decanter cake (DC) on the rumen fermentation characteristics, microbial population and nutrient digestibility. Goats were fed one of the four concentrate diets (treatments) namely, control diet (CD), decanter cake diet (DCD), palm kernel cake diet (PKCD) and CD plus 5% palm oil diet (CPOD). Feeding DCD and PKCD appeared to modify the rumen microbial population,increasing the DNA copy number of total bacteria (P < 0.01) and Ruminococcus albus (P < 0.01). The DNA copy number of Fibrobacter succinogenes was lower (P< 0.05) for the treatment CPOD compared to other treatments. The mean ciliate protozoa numbers were considerably higher for treatment CD (6.2 × 105/ml) than for other treatments (DC, DCD, PKCD and CPOD (2.1 × 105/ml)) and decreased rapidly between day 4 and 6 in goats fed treatments DCD, PKCD and CPOD. Rumen methanogenic archaea was significantly reduced in goats fed PKCD (1.50 × 109/ml) and CPOD (1.32 × 109/ml) compared to that fed CD (2.48 × 109) however, their populations in goats fed DCD (1.96 × 109/ml) and CD were similar. The trend showed a severe reduction after day 4 and 6 of the start of the feeding experimental diets. Ammonia-N concentration in rumen fluid of goats was significantly lower for treatments DCD (35.0 mg/L), PKCD (34.4mg/L) and CPOD (33.9 mg/L) than for treatment CD (49.9 mg/L) and pH was lowest for the treatment DCD (6.1) and highest for treatment PKCD (6.4). Total volatile fatty acid concentrations were significantly lower for treatment PKCD (94.8 mmol/L) and CPOD (94.4 mmol/L) than for treatment CD (98.5 mmol/L) and DCD (98.1 mmol/L). From the results obtained in the first experiment, it was concluded that inclusion of PKC and DC in the diet of goats modified the rumen microbial population by reducing ciliate protozoa and methanogenic archaea; and increasing total bacteria and some species of cellulolytic bacteria. In the second study, 32 Boer x Kacang crossbred male goats were used in a 100-day experiment. Goats were randomly assigned to one of the four dietary treatments namely, control diet (CD), decanter cake diet (DCD), palm kernel cake diet (PKCD) or control diet plus 5% palm oil (CPOD). The objective was to assess the effects of these diets on growth, carcass quality, fatty acid (FA) content of meat and nitrogen (N) metabolism. Daily weight gain was significantly lower in goats fed DCD (89 g/day) and PKCD (89 g/day) compared to those fed CD (136 g/day) and CPOD (141 g/day). Slaughter weight, and hot and cold carcass weights were higher in goats fed CPOD (34.4 kg, 16.7 kg, 16.6 kg, respectively) followed by CD (32.9 kg, 16.5 kg,16.4 kg, respectively), DCD (25.6 kg, 13.3 kg, 13.1 kg, respectively) and PKCD (24.6 kg, 11.5 kg, 11.4 kg, respectively). Nitrogen metabolism was altered in goats received PKCD, where the excretion of N in feaces was the highest (p<0.05) in goats fed PKCD (5.1 g/day) and lowest in those fed CPOD (1.6g/day). Goats fed PKCD had significantly higher C12:0 contents than those fed other diets in all muscles tested. C16:0 and C18:0 were significantly lower in muscles from goats fed CD than those fed other treatments, whereas C18:2 n-6 was highest in the muscles of goats fed CD compared to other diets. Both longissimus dorsi (LD) and infraspinatus (IS) muscles from goats fed CD had relatively lesser total saturated fatty acid (SFA) proportions; however, SFA proportions of the muscle biceps femoris (BF) was similar in all dietary treatments. Additionally, the proportions of total n-6 polyunsaturated fatty acid (PUFA), n-6: n-3 ratio and PUFA/SFA were higher in the muscles of goats fed CD than those fed other diets. It was concluded that inclusion of PKC and DC in the diet of goats up to 80% resulted in daily gain of ~90 g/day which is within reported values for goats fed such agri-industrial by-products. However, fatty acid composition of meat might be altered.